Non-obstetric surgery and anesthesia during pregnancy. Five-year single-center retrospective analysis : Non-obstetric surgery during pregnancy - Altınay, Mustafa; Çınar, Ayşe Surhan (Journal of Surgery and Medicine, 2023)
Background/Aim: Surgical procedures during pregnancy incur great difficulties for both the surgeon and the anesthesiologist. Changing maternal and fetal physiology changes both the pharmacodynamics and pharmacodynamics of the anesthetic drugs administered. In this study, the researcher aimed to determine the risk factors of non-obstetric surgery or anesthesia that cause preterm labor and/or low birth weight. Methods: Our study was planned as a single-center retrospective study and was carried out by scanning the data of 52 pregnant patients between 2015 and 2020. Preterm labor and low birth weight were defined as adverse events. The patients were divided into two groups: those who developed adverse events and those who did not. The effects of age, parity, type of surgery and anesthesia, duration of surgery, gestational age, mode of delivery, and birth weight on mortality have been investigated. Results: Comparing the patient groups with and without adverse events, no statistically significant difference was found between their general characteristics, anesthesia, and surgical characteristics (P>0.05). Conclusion: In the study, the researcher analyzed the surgical and anesthesia factors of non-obstetric surgery. It was concluded that neither surgical nor anesthetic factors independently increased the risk of preterm labor or low birth weight.